The Role of Parents in Endowing the peace concepts to their Children - Field study in Kindergarten Institutions at Tartous City - أحمد, مطيعة; نصور, رغداء; معلا غانم, أمة الله (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to definition the role of parents in endowing the peace concepts to their children in Tartous city, also tries to identify the differences in their opinions based on the following variables: (gender, scientism certificate). The present research used the descriptive analytical approach. To achieve the object of the research a questionnaire has been included (45) methods, distributed to five areas, then applied to a sample of (236) parents of kindergartens child for the academic year 2019\2020. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Tishreen and Tartous universities. Pilot sample consisted of (36) parents of kindergartens child, reliability was established by Cronbach Alpha Reliability (0.833). The research ended up with the following results: The role of parents in endowing the peace concepts to their Children in Tartous city came middle rated. No statistically significant differences regarding the role of parents in endowing the peace concepts to their children according to the gender, and there are statistically significant differences according to the scientism certificate in favor of licentiate. The research provided suggestions of endowing the peace concepts of children in Kindergartens and house, also educate parents in their constructive role in endowing peace education to their children.